"New roads – new goals. Positions of feminist planning". Frei.Räume no. 10, edited by the German FOPA (feminist organisation of (female) planners and architects) in 1998. Issue 9 (2nd September 2018) - Huning, Sandra
ABSTRACT: This Translations contribution presents the 10th issue of the series Frei.Räume (in English: Free spaces), edited by the German Feminist Organisation of (female) Planners and Architects (FOPA) in 1998. The issue was titled "New roads – new goals. Positions of feminist planning" and reflected the contemporary discussions on the state of the art of feminism, gender and planning. While progress was recognized, many authors felt uncomfortable with the ways that feminist concerns had been implemented into planning, and they were looking for ways forward. Among the authors were the most important protagonists of the debates at the time. Looking at the issue today, it becomes clear that many concerns are as up to date as they were in the late 1990s, although circumstances have changed. The paper argues that it is worthwhile to pay attention to these feminist debates in order to develop future strategies for feminism in planning.